MADZHAB RUâYAH MUSLIM AMERIKA ANALISIS ARGUMEN SYEKH HAMZAH YUSUF TENTANG PENENTUAN AWAL BULAN HIJRIYAH - Musonnif, Ahmad (Ahkam: Jurnal Hukum Islam, 2018)
ABSTRACTThe debate on how to determine the first date of Hijry month occurs in all Moslem societies. In the United States of America, Syekh Hamzah Yusuf position himself as the supporter of Ruâyah School. His article on rejecting the use of Hisab School in the United States of America encompasses his strong arguments covering the normative, historical, and scientific approaches. Because the article is written concisely and too short, it may open possibility for his opponents, the Hisab School supporters, to strongly counter his arguments. Anyway, written debates on a certain case can be an effective media for Moslem to develop the Islamic civilization.Keywords: Hisab, Ruâyah, American Moslem, Hamzah Yusuf.